Radiochemical separation of 224Ra from 232U and 228Th sources for 224Ra/212Pb/212Bi generator. (June 2021) - Pruszyński, Marek; Walczak, Rafał; Rodak, Magdalena; Bruchertseifer, Frank; Morgenstern, Alfred; Bilewicz, Aleksander
Abstract: The application of diagnostic and therapeutic radionuclides in nuclear medicine has grown significantly and has translated into the increased interest in radionuclide generators and their development. 224 Ra and its shorter-lived daughters, 212 Pb and 212 Bi, are very interesting radionuclides from Targeted Alpha Therapy point of view for treatment of small cancers or metastatic forms. The purpose of the present work was to develop a simple generator for rapid elution of carrier-free 224 Ra from 232 U or 228 Th sources by radiochemical separation based on extraction chromatography with the utilization of a home-made material. The bis(2-ethylhexyl) hydrogen phosphate (HDEHP) extractant was immobilized on polytetrafluroethylene (PTFE) grains and its ability to selectively adsorb 232 U and 228 Th, with simultaneous high elution recovery of 224 Ra, was checked over few years. The 224 Ra was quantitatively eluted with small volume (3–5 mL) of 0.1 M HNO3 with low breakthrough (<0.005%) and was used for further milking of 212 Bi and 212 Pb from DOWEX 50WX12 by 0.75 M and 2.0 M HCl, respectively. The elaborated here methods allowed high recovery of 224 Ra, 212 Pb and 212 Bi radionuclides and their application in radiolabeling of various biomolecules. Highlights: Extraction-chromatography material based on organic phosphonates on Teflon. U-232 and Th-228 were quantitatively retained on extraction chromatography column. Radium-224 was eluted in a small volume of low concentration nitric acid. Generators are stable for last 5 years without breakthrough of mother radionuclides. Bi-212 and Pb-212 were used for labeling of nanobody.